Incising and Double Impregnation of Beech Sleepers—Investigation of an Alternative Preservation System for Wooden Railway Sleepers - Starck, Michael; Heidel, Andreas; Brischke, Christian; Militz, Holger (Frontiers in Forests and Global Change, 2022)
For nearly 200 years wooden railway sleepers are impregnated with creosote. After initially using vacuum pressure processes for impregnation, empty-cell processes have been developed quickly and are used until today. Because of political developments, creosote will probably be banned on the European market and elsewhere in the near future. The Fürstenberg-System-Sleeper, which combines a mechanical pre-treatment (incising), a double impregnation of sleepers including an alternative oily wood preservative and a water-borne copper salt as well as a modernized quality control shall on the one hand serve as an alternative to creosoted sleepers and on the other hand ensure future use of wooden sleepers in track superstructure. Incising reduced the formation of checks in sleepers made from European beech (Fagus sylvatica L.) until they are dry enough for impregnation, but did not decrease the drying time or the number of sleepers being culled based on excessive deformation. Additionally, positive effects on preservative retention and -penetration were observed. During double impregnation with the water-borne preservative first and the oily preservative afterwards, it became evident, that a gross weight of at least 950 kg/m³ was needed for penetrating the peripheral area of the sleepers to achieve an additional homogenous envelope treatment.